Greek drama - Hadas, Moses, 1900- (New York : Bantam Books, 1982)
Contents : Aeschylus. Agammemnon. Eumenides.--Sophocles. Antigone. Oedipus the King. Philoctetes.--Euripides. Medea. Hippolytus. Trojan women.--Aristophanes. Frogs.
Keywords: Greek drama